Origins How the Planets, Stars, Galaxies, and the Universe Began - Eales, Stephen; SpringerLink (Online service) (London : Springer London, 2007)
The biggest questions in astronomy are those of how the planets, stars, galaxies, and the Universe were formed. ORIGINS describes how over the last decade, astronomers have discovered the probable answers to three of these fundamental questions. Starting with the space missions that have uncovered the haphazard history of our own planetary system, this book travels into space and backwards in time, describing the discovery of other planetary systems and their connection to extraterrestrial life. The first moments in the life of a star are covered, along with the birth of galaxies, and the biggest question of all - the origin of the Universe itself. ORIGINS also tells the human stories behind the discoveries: the astronomers who searched for Planet X but lost a planet, the cosmic archaeologists who deciphered the history of galaxies, and of boomerang, the telescope that came back and showed that space is flat.
Planets -- Rocks -- The Day the Solar System Lost a Planet -- ET and the Exoplanets -- Stars -- Connections -- The Final Frontier -- Galaxies -- Silent Movie -- The History of Galaxies -- The Universe -- Watching the Big Bang on Television -- Plato$1 (Bs Ghost.s
Keywords: Physics; Observations, Astronomical; Astronomy -- Observations; Cosmology; Astronomy; Physics; Cosmology; Astronomy, Observations and Techniques; Popular Science in Astronomy; Electronic books